Analisis Perilaku Check-Out di Rumah Susun Sederhana Sewa Universitas Diponegoro - Rifka Agri Setyawan; Arif Pujiyono (Diponegoro Journal of Economics, 2020)
One of the various rental housing options in Tembalang is the rental public housing (Rusunawa) of Diponegoro University (UNDIP), which is located on Jalan Profesor Soedarto S.H., Tembalang, Semarang. Rusunawa UNDIP has a relatively cheap rental price compared to rental housing around the UNDIP campus, in addition to the Rusunawa UNDIP is also equipped with several supporting facilities. Although it has a relatively cheap residential rental price and is equipped with adequate facilities, the UNDIP Flat Housing has not been matched with optimal housing demand and also has a high level of occupants deciding to check out. So that this study has the purpose of finding out what is behind the phenomenon, occurring in the flat of UNDIP. This kind of behavior is interesting and important to do research. This research wasconducted with a qualitative method of phenomenological perspective, precisely Interpretative Phenomenological Analysis (IPA). The subjects of this study were five people and the sampling was done using purposive technique, where all of them were former residents of the Rusunawa UNDIP. The beginning of the study was interview activities with the research subjects, from which interviews were obtained transcripts of interviews which then from the transcripts were recorded to compile emergencies themes, super-ordinate themes, and parent themes. The results of the study obtained four main themes which also explained the background of the occurrence of the phenomenon of the low demand for rent in Rusunawa UNDIP because of management factors, infrastructure, social environment, location, and physical building.